Thermal Shock Fabrication of Ion‐Stabilized Perovskite and Solar Cells. Issue 32 (10th July 2022) - Kang, Yifei; Wang, Anran; Li, Rong; Song, Yilong; Wang, Xinjiang; Li, Hanming; Xu, Weiqing; Zhang, Lijun; Dong, Qingfeng
Abstract: A highly crystalline tempered‐glass‐like perovskite grain structure with compressed surface lattice realized by a thermal‐shocking fabrication is shown. The strained perovskite grain structure is stabilized by Cl − ‐reinforcing surface lattice and shows enhanced bonding energy and ionic activation temperature, which contributes to hysteresis‐free operation of perovskite solar cells (PSCs) at much higher temperature up to 363 K in thermal‐shocking‐processed MAPbCl x I3− x (T‐MPI). The PSCs can be fabricated by a high‐speed fully air process without post‐annealing based on the scalable bar‐coating technique. Both high efficiency and stability are achieved in T‐MPI PSC with a power conversion efficiency (PCE) up to 22.99% and long‐term operational stability with T 80 lifetime exceeding 4000 h. Abstract : A highly crystalline tempered‐glass‐like perovskite with compressed surface lattice‐structure can be made by a thermal‐shocking fabrication process, which significantly enhances the ionic activation temperature and contributes to hysteresis‐free operation of perovskite solar cells (PSCs) at high temperature up to 363 K, enabling efficient and stable PSCs fabricated by a high‐speed post‐annealing‐free process in air with the scalable bar‐coating technique.